Filarial excretory-secretory products induce human monocytes to produce lymphangiogenic mediators. - Tiffany Weinkopff; Charles Mackenzie; Rob Eversole; Patrick J Lammie (Public Library of Science (PLoS), 2014)
The nematodes Wuchereria bancrofti and Brugia spp. infect over 120 million people worldwide, causing lymphedema, elephantiasis and hydrocele, collectively known as lymphatic filariasis. Most infected individuals appear to be asymptomatic, but many exhibit sub-clinical manifestations including the lymphangiectasia that likely contributes to the development of lymphedema and elephantiasis. As adult worm excretory-secretory products (ES) do not directly activate lymphatic endothelial cells (LEC), we investigated the role of monocyte/macrophage-derived soluble factors in the development of filarial lymphatic pathology. We analyzed the production of IL-8, IL-6 and VEGF-A by peripheral blood mononuclear cells (PBMC) from naïve donors following stimulation with filarial ES products. ES-stimulated PBMCs produced significantly more IL-8, IL-6 and VEGF-A compared to cells cultured in medium alone; CD14(+) monocytes appear to be the primary producers of IL-8 and VEGF-A, but not IL-6. Furthermore, IL-8, IL-6 and VEGF-A induced in vitro tubule formation in LEC Matrigel cultures. Matrigel plugs supplemented with IL-8, IL-6, VEGF-A, or with supernatants from ES-stimulated PBMCs and implanted in vivo stimulated lymphangiogenesis. Collectively, these data support the hypothesis that monocytes/macrophages exposed to filarial ES products may modulate lymphatic function through the secretion of soluble factors that stimulate the vessel growth associated with the pathogenesis of filarial disease.